Educational Factors in the Shahnameh of Ferdowsi and Its Influence on Western Literature A Comparative Vision between Ferdowsi and Baltasar Gracian - Beatriz Salas (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study presents the possible and hitherto unknown or little spread influence of the Shahnameh of Ferdowsi on the Spanish writer and educator Baltasar Gracián, and consequently, the projection of Ferdowsi in modern western thought through certain European philosophers and thinkers of special importance. In a comparative vision of aspects of the works of both authors, an attempt will be made to support Ferdowsi’s legacy to Western thought, specifically in the educational and moral aspects.